Digital Literacy Learning Management Innovation at State Vocational Schools in Manado City - Koessoy, Herman; Katuuk, Deitje Adolfien; Lengkong, Jeffry S J; Rotty, Viktory Nicodemus Joufree (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This article aims to describe innovations in digital literacy learning management for students at State Vocational Schools in Manado City. This research is a qualitative research in which the data collection process is carried out through interviews, observation and documentation. From the research conducted, it is known that SMK schools in Manado City innovate in 3 ways, namely: Changing the teacher's paradigm of conventional education towards modern education with education and training activities and educational seminars and through improving academic qualifications, secondly Providing digital literacy skills to teachers, education staff and students through digital literacy workshops and training activities related to the use of the latest learning and learning media and technology and the third is by providing facilities and infrastructure that can be utilized by students, teachers and education staff to support digital literacy activities in the school environment. This method is considered appropriate and quite successful in encouraging all components of the school to learn and improve their respective human resources regarding digital literacy.